Patterns of behavior of users of an emergency service addorsed to a Type 4 Hospital - Galaz, César; Godoy, Rodrigo; Cisternas, Javier; Yentzen, Gladys; De la Fuente, María (Revista Chilena de Salud Pública, 2004)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Study carried out f in the Llay Llay Hospital to determine the relation between user perception of emergency and medical care provided. Characteristics of the E111ergenc.v Service users are described and a personal interview is carried out. The following were defined: User Perception: Urgent and Non-urgent; Urgent and Non-urgent Medical Attention; Infrequent or Frequent User or Polyconsultant. The population presents similar consultancy levels throughout the year, no rises being observed pointing to higher consultancy periods; also, there exists a preference for consulting on Mondays, with a slackening toward Saturdays and Sundays. Of the 104 persons interviewed for this study, the majority were women. Average age was 42 years, there being no difference between sexes. There was coincidence both in care preference and where the interview took place. Reasons for preferring the Emergency Service include: rapid resolution, previous appointment not required, and immediate taking of exams. Reasons for choosing the Clinic include: free delivery of pharmaceuticals and conformity with medical care received. Waiting time was not considered a factor having an influence on the choice. The existence of factors not related to a need for immediate care was proved: 28.6% of males and 34.4% of females attended the Emergency Service with a "non-urgent user perception". Among the "non-urgent" options suggested, lack of availability of outpatient hours in the Clinic and use of the Emergency Service only due to personal preference, stand out. Upon evaluating the discriminative capacity between "urgent" and "non-urgent", sensitivity is 78% and .specificity is 55%, the "false positive" are 17% and the "false negative", 52%. The percentage of "frequent patients" is around 50% with a 6.1% of "polyconsultants" and a 14% of "hospitalizations ". The conclusion is that predictable and quantifiable user patterns of behavior would exist that would allow for the implementation of measures that would induce a good use of Emergency Services.